Foreign market entry under incomplete contracts - Tobias Seidel (Center for Economic Studies and ifo Institute (CESifo), 2010)
I show in this paper that incomplete contracts affect a firm's decision about serving foreign customers through exports or local sales from an affiliated plant. When contracts between two agents within a firm are too costly to write, the share of multinational firms may be higher or lower compared to a world without contractual frictions. Incomplete contracts also provide a novel explanation for why horizontal multinational activity may increase when trade costs fall - a result that is at odds with the proximity-concentration trade-off.
Keywords: F12; F15; F23; 330; multinational firms; exports; incomplete contracts; Internationale Markteintrittsstrategie; Multinationales Unternehmen; Export; Unvollständiger Vertrag; Theorie